2022
DOI: 10.1007/s00170-022-09674-3
|View full text |Cite
|
Sign up to set email alerts
|

Twist springback and microstructure analysis of PEEK sheets in ultrasonic-assisted thermal incremental forming

Abstract: With a view to reducing the springback and twist of PEEK during the incremental forming process, the ultrasonic vibration is introduced into polymer thermal SPIF. In this study, the effects of temperature and ultrasonic vibration on twist and springback of formed parts are investigated. Several modi ed tool trajectories are developed, and the in uence of tool trajectory on twist and springback are also studied.Finally, the microstructures of PEEK parts are analyzed by XRD. The results show that the increase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The results revealed that the incremental forming process reduced the springback and twist of PEEK. The optimized tool trajectory could effectively eliminate warpage and reduce springback of PEEK parts [23].…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the incremental forming process reduced the springback and twist of PEEK. The optimized tool trajectory could effectively eliminate warpage and reduce springback of PEEK parts [23].…”
Section: Introductionmentioning
confidence: 99%
“…Ghafoor S. et al [16] used ultrasonic vibration to effectively improve the forming forces, relieve the stress concentration phenomenon, and reduce the forming geometry errors. Liao J. et al [17] investigated the effect of temperature and ultrasonic vibration on the forming accuracy of PEEK sheets and showed that ultrasonic vibration at 60°C and 100°C helped to refine the grains and improve the accuracy. Praveen K. et al [18] used double-sided incremental forming to improve the forming accuracy by customizing the tool to apply specific support forces on the bottom surface.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of elastic modulus was affected by both the initial stress and residual stress, which resulted in a nonlinear shift in the stress path. Liao et al [26] study on the improved molding process for PEEK-optimized tools sought to eliminate springback and distortion. The distortion of PEEK components and springback were successfully reduced.…”
Section: Introductionmentioning
confidence: 99%